Gut microbiota in patients with sarcopenia: a systematic review and meta-analysis - Wang, Guangning; Li, Yujie; Liu, Huisong; Yu, Xinjuan (Frontiers in Microbiology, 2025)
BackgroundIntestinal dysbiosis was considered a pivotal pathological mechanism underlying sarcopenia. Despite the fervor surrounding research in this domain, substantial controversy persists regarding the obtained outcomes.ObjectiveTo systematically summarized the disparities in gut microbiota composition between the group afflicted by sarcopenia and non-sarcopenia controls.MethodsPubMed, Medline, CINAHL, EMBASE, Scopus, Web of Science and Google Scholer, Cochrane Library and gray literature sources were systematically searched for in randomized controlled trials. Meta-analysis and random-effects meta-regression were conducted using Rev. Man 5.3. Overall effect was measured using Hedges’s g and determined using Z-statistics. Cochran’s Q test and I2 were used to investigate heterogeneity. The Newcastle-Ottawa Scale was used to assess overall quality of evidence.ResultsTen studies, including 421 cases of sarcopenia and 1,642 cases of controls, were included in the meta-analysis. Patients with sarcopenia showed significantly reduced gut microbiota in α diversity, and β diversity was significantly different in 8/9 of included studies. We also found more abundance of phylum Proteobacteria and genus Escherichia-Shigella, and less abundance of phylum Firmicutes and genus Faecalibacterium, Prevotella 9, Blautia in the sarcopenia group.ConclusionThe gut microbiota composition in patients with sarcopenia has undergone alterations, serving as a fundamental reference for further investigation into the potential pathogenic mechanisms and treatment strategies for sarcopenia.